Enteric Function as a Determinant of Nutritional and Clinical Recovery from Acute Illness Among Children in Kenya and Pakistan. (29th May 2020) - Tickell, Kirkby; Denno, Donna; Saleem, Ali; Kazi, Zaubina; Richardson, Barbra; Achieng, Catherine; Mutinda, Charles; Ochuodho, Victor; Oduol, Chrisantos; Berkley, James; Singha, Benson; Walson, Judd
Abstract: Objectives: In low- and middle-income countries (LMICs), acutely ill undernourished children remain at high risk of mortality for months following discharge from hospital. Community-based studies suggest that enteric dysfunction (ED), including permeability and impaired absorption, is associated with poor outcomes. We used the lactulose rhamnose ratio (L: R) test, which provides a functional assessment of gut integrity, to determine if ED influences clinical and nutritional recovery in the post-discharge period. Methods: Children aged 2–24 months without diarrhea were recruited from Civil Hospital Karachi, Pakistan and Migori County Referral Hospital, Kenya. L: R tests were administered after children were clinically stable (oral feeds, not dehydrated, no oxygen needs) and pre-discharge. Similarly aged children were pseudo-randomly selected from homes near those of children being discharged and were also tested. Prior to administration of sugars, urine was collected to detect background levels, followed by a two-hour collection. Samples were analyzed by high-performance chromatography mass spectroscopy. Crude L: R distributions were compared using the Mann-Whitney test. A priori determined confounders (age, mid-upper arm circumference [MUAC], HIV status, site) were adjusted for in linear regression of log-transformed L: R. Results: 156 hospitalized and 91 community children were recruited. Median age was nine months in each group. Hospitalized children had lower median MUAC (12.4 vs 13.5 cm) and higher HIV infection prevalence (5% vs 1%). Both sugars were largely undetectable in pre-dose samples. Urinary median L: R among children being discharged (0.36 (interquartile range [IQR] 0.20–0.87)) was significantly higher compared to community peers (0.30 (IQR: 0.17–0.48, P  = 0.038)). This difference remained significant in the adjusted model (p: 0.008). Conclusions: Children at discharge from hospital in LMICs appear to have worse enteric function than community peers, and this difference does not appear to be attributable to young age or nutritional or HIV status. This analysis will be expanded to include L: R association with mortality, morbidity and growth outcomes prior to the conference. Funding Sources: Thrasher Research Foundation 14, 466, the Bill & Melinda Gates Foundation OPP 1, 131, 320.